Nursing care to the amputee's health (Research, Society and Development, 2022)
Objective: to identify the importance of Nursing care to the amputated patient. Methods: this is an integrative review study, which allows the synthesis of multiple published studies. Results: no hospital before the nurse's procedure should carry out all the client's history, exams examined, identify and treat any health problem that may hinder the verification of the surgical act and emotionally support the patient and family, in the face of loss of the limb, explaining the procedure and rehabilitation, the nurse seeks to observe and guide regarding the changes that must be made at the patient's home, in nursing consultations, physical and psychosocial adaptation must be evaluated and continue performing the physical examination and regular diagnostic tests Conclusion: in view of the above, it is concluded that the nurse is in charge of offering assistance, promoting a better quality of life, in aspects related to its realization as well as family and social relationships, in addition to emotional issues and daily difficulties. Assistance to amputee patients encompasses a range of factors where the professional must have a holistic view of this individual.